Solution blow spinning control of morphology and production rate of complex superconducting YBa 2 Cu 3 O 7−x nanowires - Rotta, M. [UNESP]; Motta, M.; Pessoa, A. L. [UNESP]; Carvalho, C. L. [UNESP]; Ortiz, W. A.; Zadorosny, R. [UNESP] (Springer Nature, 2019)
Nanostructured materials have the potential to be applied in different areas ranging from electronics to medicine. Techniques for preparation of nanomaterials with a high production rate are essential to make them commercially available. In this work, complex superconducting YBa 2 Cu 3 O 7−x wires were prepared by using the solution blow spinning technique with different solution injection rates (SIRs): 60, 80 and 100 μL/min. We show that the diameter of the YBCO wires increases from 258 to 954 nm for higher SIRs without any trace of secondary phases as investigated by X-ray diffractograms. Nonetheless, SIR does not supply the real ceramic production rate, which is 4.7 to 33 times higher than the rates of equivalent ceramics produced by Electrospinning. Furthermore, the magnetic properties of the YBCO wires were verified, presenting similar superconducting responses.